Randomised Controlled Trial on the Effect of Psychoeducation on Expressed Emotion of Caregivers of Individuals with Schizophrenia and its Association with Patient Outcome in Maiduguri, Northeastern Nigeria - Suleiman Awwal Muhammed; Nada Abdulwahab Said; Abdulrahman Ashiru; Bello Umar; Shefa’atu Shehu; Fatima Gambo Kaigama; Jidda Mohammed Said; Musa Abba Wakil (International Journal of Recent Advances in Multidisciplinary Topics, 2026)
Schizophrenia affects about 24 million people worldwide, representing 1 in 300 individuals (0.32%). A 2010 Nigerian study reported a lifetime prevalence of 2.1%. Although relatively low, the disorder imposes a significant and growing burden on healthcare systems in low- and middle-income countries due to population growth and aging. Despite treatment advances, relapse rates remain high, influenced by prolonged illness duration, medication non-adherence, substance use, stressful life events, comorbid mental illness, and psychosocial factors such as expressed emotion (EE). High EE, marked by critical comments, hostility, and emotional over-involvement from caregivers, is strongly linked to relapse in schizophrenia and evidence indicates that psychoeducation reduces high EE. Thus, family psychoeducation is a vital intervention to lower relapse rates and ease the global schizophrenia burden. The aim of the study is to evaluate the effect of psychoeducation on the level of expressed emotion among caregivers of individuals with schizophrenia and its associated patient outcome. The study was a randomized controlled trial to evaluate the effect of psychoeducation on caregiver EE levels and patient outcomes among individuals with schizophrenia attending the Federal Neuropsychiatric Hospital, Maiduguri. Sixty-two patient-caregiver pairs, diagnosed using the MINI, were randomized into intervention and control groups via permuted block randomization. Baseline assessments employed the Levels of Expressed Emotion Scale (LEES) and Positive and Negative Syndrome Scale (PANSS). The intervention group participated in three sessions of family psychoeducation, while the control group received standard treatment. Post-intervention assessments were conducted at 2 weeks and 6 months. The prevalence of high expressed emotion (EE) was 53.2%. Psychoeducation significantly reduced EE levels after 2 weeks compared with the control group (mean difference = 9.00, p < 0.001; Cohen's d = 1.001). However, relapse rates (3.2%) did not differ significantly between the groups after 6 months. Family psychoeducation effectively reduced EE and may improve caregiver and patient outcomes.